Influence of the radius of Monson’s sphere and excursive occlusal contacts on masticatory function of dentate subjects - Carneiro, Dominique Ellen; Zander, Luiz Ricardo Marafigo; Ruppel, Carolina; De La Torre Canales, Giancarlo; Auccaise-Estrada, Rubén; Sánchez-Ayala, Alfonso (Archives of oral biology, 2024)
To determine the influence of the radius of Monson’s sphere, the number of posterior laterotrusive, mediotrusive, and protrusive contacts, and the chewing rate on food comminution. Sixty healthy dentate subjects, aged 21.22 ± 2.30 years, were selected. The three-dimensional coordinates of the cusp tips of the lower canine, premolar, and molar teeth were identified from the subjects’ digital models. Monson’s sphere was designed using the simplex method for function minimisation by adjusting the coordinates on its surface. The contacts were verified using 12 µm metal strips in jaw excursions at 0.5, 1.0, 2.0, and 3.0 mm. The masticatory performance and efficiency, swallowing threshold, and chewing rate were assessed through particle size fractionation. Data were analysed with multiple linear regression (α = 0.05). The sphere’s radius, laterotrusive and protrusive contacts at 0.5 mm, and chewing rate were found to be negative predictor variables for masticatory performance until 20 chewing cycles (R2 = 0.429). For 40 cycles, the radius and total contacts (0.5 mm) were also explanatory factors (R2 = 0.223). Only the radius (R2 = 0.176) and the chewing rate (R2 = 0.082) were found to be significant for 60 cycles and swallowing threshold, respectively. Masticatory efficiency was influenced by masticatory performance until 40 and 60 cycles, as well as the radius and total contacts at 2.0 and 3.0 mm (R2 = 0.958). A larger radius of Monson’s sphere and a greater number of posterior excursive contacts were found to be related to better masticatory function. •Improved mastication was influenced by a larger radius of Monson’s sphere.•The radius and 0.5-mm latero-protrusive contacts affected chewing up to 20 cycles.•The explanatory factors for 40 cycles were the radius and total contacts at 0.5 mm.•The radius and chewing rate altered mastication (60 cycles) and swallowing threshold.•Masticatory efficiency was influenced by the radius and contacts at 2.0 and 3.0 mm.